The war and mobilization on Ottoman people during the Caucasus war and Indonesian Independence Day 1945-1949 - Sihombing, Goki Pangihutan; Octavian, Amarulla (Jurnal Politik Indonesia: Indonesian Political Science Review, 2021)
This study is to find out the history of people's mobilization by the Ottoman Empire in the Caucasus war in 1914-1918 and its relation to how people's mobilization was carried out in the Indonesian War of Independence in 1945-1949. The method in this study uses a qualitative-exploratory method supported by the theory of war, the theory of nationalism, and the theory of Defense Management. The study results show similarities and differences between the mobilization of the Ottoman people in the Caucasus War and the mobilization of the Indonesian people in the War of Independence. Then it was found that the mobilization of the people carried out by the Ottoman Empire in the form of policies of the Empire's leaders and declarations of Muslim religious figures amounted to 2.87 million people out of 23 million population (12.39%) and in the mobilization of the Indonesian people during the War of Independence amounted to 37.76 million out of 75.53 million. The number of residents (50%) was carried out through speeches and orations from warrior figures by igniting the spirit to participate in the struggle to fight against the British and Dutch by prioritizing the high fighting spirit of nationalism simultaneously and universally throughout the territory of Indonesia.